Developing the multi-dimensional mobility divide index (MDI) as a methodology to assess the accessibility level of public transport systems [version 1; peer review: 2 approved] - Cino Repetto; Florian Brinkmann; Leonardo Benzi; Alexey (Aliaksei) Andrushevich; Tally Hatzakis; Alexandra Koenig; Martina Bagnasco; Laura Alčiauskaitė (Open Research Europe, 2022)
Background: This paper presents the development of a multi-dimensional mobility divide index (MDI) for assessing the accessibility of public transport developed using a co-design approach, directly involving end-users in the index design process. The index measures the gap that persons with disabilities feel they need to over-come to use public transport in the same way non-disabled citizens do. The MDI covers six accessibility-related dimensions: 1) safety, 2) convenience, 3) comfort, 4) affordability, 5) travel time, and 6) autonomy. Methods: The method paper describes the step-by-step approach to create the MDI as a set of indicators to be rated by people with different access needs to 1) provide evidence of the main criticalities to be addressed through the design and implementation of new inclusive mobility solutions, 2) guide the design of new inclusive mobility solutions and measure their impacts, and 3) inform the transport sector encouraging positive changes in transport by providing recommendations for policy-making, new directions for service innovation, improvements and practical advice or highlighting investment priorities to pave the way for a more inclusive mobility. Results: We present our findings in ways that can inform universal design and provide actionable information to researchers, policymakers, transport and urban planners, operators, and stakeholders’ representatives to promote inclusive and equitable mobility solutions for all. Conclusions: Finally, we suggest follow up research and innovation, as well as recommendations for its uptake and utilisation in the pursuit of European accessibility standards and requirements for products and services in the mobility sector.